1994
DOI: 10.1084/jem.179.4.1307
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of integrin-mediated adhesion of T lymphocytes and monocytes: two mechanisms with divergent biological consequences.

Abstract: SummaryWe show that the adhesion of T lymphoid cells to immobilized fibronectin can be increased by two distinct mechanisms. The first is by increasing the affinity of the fibronectin receptor/ligand interaction using the antiq~l integrin monodonal antibody 8A2. The second is by treating the ceUs with phorbol 12-myristate 13-acetate (PMA), which alters events that occur after receptor occupancy (e.g., cell spreading) without affecting receptor affinity. The effects of these two mechanisms on adhesion in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 73 publications
10
82
0
Order By: Relevance
“…Thus, the high-affinity ␣ 4 ␤ 1 on Jurkat cells do not appear to play a major role in regulating static cell adhesion. This finding is not unique to ␣ 4 ␤ 1 , as integrin ␣ 5 ␤ 1 activation also plays only a minor role in static cell adhesion (21). Furthermore, wild-type and ␣ 4 ␤ 1 activation-defective Jurkat cells showed similar tethering/rolling and adhesion strengthening on VCAM-1 under flowing conditions.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, the high-affinity ␣ 4 ␤ 1 on Jurkat cells do not appear to play a major role in regulating static cell adhesion. This finding is not unique to ␣ 4 ␤ 1 , as integrin ␣ 5 ␤ 1 activation also plays only a minor role in static cell adhesion (21). Furthermore, wild-type and ␣ 4 ␤ 1 activation-defective Jurkat cells showed similar tethering/rolling and adhesion strengthening on VCAM-1 under flowing conditions.…”
Section: Discussionsupporting
confidence: 52%
“…This interpretation is supported by previous findings that integrin-mediated adhesion is mediated by a rapid increase of the affinity of these molecules towards their respective ligands. 14,47 However, the fact that the anti-CD19-induced aggregation could be blocked by cycloheximide demonstrated that initiation of homotypic adhesion also depended on protein synthesis. The activity of integrin molecules is influenced by a large number of regulatory proteins (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Avidity changes, which include integrin clustering, association with the cell cytoskeleton, and activation-dependent cell spreading, up-regulate integrin ligand binding without affecting affinity. Phorbol ester treatment of T cells triggers ␤ 1 and ␤ 2 integrin-mediated adhesion and cell spreading in the absence of changes in integrin affinity (14,15). Similarly, cross-linking the TCR complex induces cell flattening, association of integrins with cytoskeletal proteins, and adhesion to VCAM-1 and ICAM-1 without altering integrin affinity (15)(16)(17).…”
mentioning
confidence: 99%